Preliminary Results of Marine Electromagnetic Sounding with a Powerful, Remote Source in Kola Bay off the Barents Sea. (20th February 2013) - Grigoryev, Valery; Korotaev, Sergey; Kruglyakov, Mikhail; Orekhova, Darya; Scshors, Yury; Tereshchenko, Evgeniy; Tereshchenko, Pavel; Trofimov, Igor
Abstract : We present an experiment conducted in Kola Bay off the Barents Sea in which new, six-component electromagnetic seafloor receivers were tested. Signals from a powerful, remote super-long wave (SLW) transmitter at several frequencies on the order of tens Hz were recorded at the six sites along a profile across Kola Bay. In spite of the fact that, for technical reasons, not all the components were successfully recorded at every site, the quality of the experimental data was quite satisfactory. The experiment resulted in the successful simulation of an electromagnetic field by the integral equation method. An initial geoelectric model reflecting the main features of the regional geology produced field values that differed greatly from the experimental ones. However, step-by-step modification of the original model considerably improved the fit of the fields. Thereby specific features of the regional geology, in particular the fault tectonics, were able to be corrected. These preliminary results open the possibility of inverse problem solving with more reliable geological conclusions.